Ultrasound Microwave Assisted Extraction On Citronella Leaves Using Ionic Solvent: Ultrasound Microwave Assisted Extraction Pada Daun Serai Wangi Menggunakan Pelarut Ionik - Wicaksono, Akhmad Permadi; Afandi, Fadila Ardiansyah; Pujiastuti, Caecilia; Erliyanti, Nove Kartika; Panjaitan, Renova (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2024)
Leaves of citronella (Cymbopogon nardus L.) have pretty much essential oil. Essential oil from citronella leaves is generally extracted by conventional methods. Conventional method is still less effective. The problem can be overcome by using non-conventional methods in the form of UMAE (Ultrasound-Microwave Assisted Extraction). UMAE is an extraction process assisted by ultrasound and microwaves. NaCl solution can be used as a solvent in the UMAE method because NaCl has a large dielectric constant. The aim of this study was to examine the effect of extraction time and the addition of salt on the yield and color of essential oils produced using the UMAE. The extraction process begins with the raw material preparation stage, such as harvesting, size reduction, and drying. Then, pre-treatment was carried out using ultrasound for 5 minutes at 35oC with the addition of 2, 4, 6, 8, and 10% (w/v) salt. Pre-treatment results were followed by the extraction process using microwaves for 30, 45, 60, 75, and 90 minutes. The best results were obtained with the addition of 6% salt and 60 minutes of extraction time with a feed to solvent ratio of 0.1 with a yield of 1.975%. and the color is yellow.